Kidney health for everyone everywhere - from prevention to detection and equitable access to care - Li, Philip Kam-Tao; Garcia-Garcia, Guillermo; Lui, Siu-Fai; Andreoli, Sharon; Fung, Winston Wing-Shing; Hradsky, Anne; Kumaraswami, Latha; Liakopoulos, Vassilios; Rakhimova, Ziyoda; Saadi, Gamal; et al. (African Journal of Nephrology, 2020)
The global burden of chronic kidney disease (CKD) is rapidly increasing, with a projection of becoming the 5th most common cause of years of life lost globally by 2040. Aggravatingly, CKD is a major cause of catastrophic health expenditure. The costs of dialysis and transplantation consume up to 3% of the annual healthcare budget in high-income countries. Crucially, however, the onset and progression of CKD is often preventable. In 2020, the World Kidney Day campaign highlights the importance of preventive interventions – be it primary, secondary or tertiary. This article focuses on outlining and analyzing measures that can be implemented in every country to promote and advance CKD prevention. Primary prevention of kidney disease should focus on the modification of risk factors and addressing structural abnormalities of the kidney and urinary tract, as well as exposure to environmental risk factors and nephrotoxins. In persons with pre-existing kidney disease, secondary prevention, including blood pressure optimization and glycemic control, should be the main goal of education and clinical interventions. In patients with advanced CKD, management of co-morbidities such as cardiovascular disease is a highly recommended preventative intervention to avoid or delay dialysis or kidney transplantation. Political efforts are needed to support the preventive approach. While national policies and strategies for non-communicable diseases might be present in a country, specific policies directed toward education and awareness about CKD screening, management and treatment are often lacking. Hence, there is an urgent need to increase the awareness of the importance of preventive measures among populations, professionals and policy makers.